Preparation of fluorescent thermoplastic polyurethane microcellular foam films blown by supercritical CO2. (September 2019) - Wang, Shiping; Xue, Shuaiwei; Ge, Chengbiao; Ren, Qian; Zhao, Dan; Zhai, Wentao
In this study, the microcellular thermoplastic polyurethane foam with excellent fluorescent performance and a density of about 0.32 g/cm 3 was prepared using solid-state foaming technology. The micro-sized green fluorescent pigment not only endowed thermoplastic polyurethane film with color, but also acted as nucleating agent to influence the cell morphology of thermoplastic polyurethane foam. Laser scanning confocal microscopy testing demonstrated that the characteristic excitation and emission peaks were observed in thermoplastic polyurethane/fluorescent pigment films and foams at 465 and 510 nm, respectively. It is found that the specific intensity of the characteristic emission peak was higher than that of the unfoamed counterpart, resulting from the formation of skin-core structure in thermoplastic polyurethane foam. By adjusting the thickness of unfoamed skin layer, the fluorescent performance of thermoplastic polyurethane / fluorescent pigment foam could be optimized.